2008
DOI: 10.2166/wh.2009.004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of performance-based training

Abstract: This article describes a statistical analysis of small water systems' turbidity data within the framework of a logic model for the USEPA's Performance-Based Training (PBT) program. The logic model shows the theoretical linkages between optimization training for small system operators; operator application of optimization techniques; improvements in plant filtration performance; and public health protection. The analysis comprised two phases. For the first phase, the authors used Bayesian analysis of turbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Findings from this study show that the monetized benefits provided by reduced cases of gastroenteric disease exceeded the required investments by a factor of between 3 and 10, depending on how the health benefits were monetized. Bowman et al (2009) offered further evidence that additional investments in small systems can yield results. They reported that a performance‐based training system for small system operators significantly improved finished water turbidity and estimated that such training efforts can reduce the incidence of cryptosporidiosis by 10 cases per 1,000 customers.…”
Section: Small Systemsmentioning
confidence: 95%
“…Findings from this study show that the monetized benefits provided by reduced cases of gastroenteric disease exceeded the required investments by a factor of between 3 and 10, depending on how the health benefits were monetized. Bowman et al (2009) offered further evidence that additional investments in small systems can yield results. They reported that a performance‐based training system for small system operators significantly improved finished water turbidity and estimated that such training efforts can reduce the incidence of cryptosporidiosis by 10 cases per 1,000 customers.…”
Section: Small Systemsmentioning
confidence: 95%
“…Reduction of turbidity during drinking water treatment processes has been shown to be significantly correlated with removal of Giardia cysts and Cryptosporidium oocysts in both pilot [245] and full-scale [246] treatment facilities. Efforts to improve the quality of drinking water by more effective filtration through regulation [247] and through operator training [248] were predicated on turbidity reduction and associated removal of protozoan cysts and oocysts. Periodic measurements of the turbidity of both challenge water and product water during testing of a POU/HWT device may provide useful indications of the performance of the system.…”
Section: Operational Monitoring Of Point-of-use Systems During Testingmentioning
confidence: 99%